Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1055/s-0029-1186141
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effect of Meso-2,3-Dimercaptosuccinic Acid and Allicin on Blood and Tissue Lead Content in Mice

Abstract: It has been shown that garlic and its main bioactive component, allicin, as natural chelating agents can reduce blood and tissue lead content in animal models. In this study the effect of allicin, alone or combined with meso-2,3-dimercaptosuccinic acid (DMSA), in decreasing lead content of blood and tissues of mice was evaluated. Swiss albino mice were exposed to 1000 ppm of lead in water for 35 days and then placed in various treatment groups including groups administered oral allicin, DMSA, or their combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Aslani et al. [46] showed that blood and tissue lead concentrations in mice are reduced when they are treated simultaneously with oral allicin and DMSA. They proposed that allicin acts as a chelating agent in the treatment of lead poisoning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslani et al. [46] showed that blood and tissue lead concentrations in mice are reduced when they are treated simultaneously with oral allicin and DMSA. They proposed that allicin acts as a chelating agent in the treatment of lead poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is presumable that garlic ingredients (allicin or alliin) through their biologically active agents, such as thiosulfinate or amino functional groups, act through similar mechanisms as those of chelators like DMSA, penicillamine, dimercaprol and calcium edetate (Ca-EDTA) to facilitate the excretion of lead from the body. Aslani et al [46] showed that blood and tissue lead concentrations in mice are reduced when they are treated simultaneously with oral allicin and DMSA. They proposed that allicin acts as a chelating agent in the treatment of lead poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic is shown to possess higher antioxidant potential than onion [ 59 ] which may be associated with the presence of allicin [ 7 ]. Aslani et al (2010) [ 6 ] have shown that the administration of the mixture of garlic extract and dimercaptosuccinic acid (DMSA) may be able to very effectively ameliorate the rats suffering from lead poisoning. In addition to many health benefits, garlic also acts as a booster of immunity and contains antiaging substance(s) [ 60 ].…”
Section: Phytochemicals Used In Amelioration Of Heavy Metals Inducmentioning
confidence: 99%
“…Therefore, methods for reducing the side effects of chelation therapy have been studied based on the use of natural products or foods (Gupta et al 2015), essential metals, vitamins, phytochemicals, or probiotics (Zhai et al 2015). Representative phytochemical antidotes for heavy metal induced toxicity include allicin from garlic (Aslani et al 2010;Shahsavani et al 2011), anthocyanin from cherry, grapes and berries , catechins from tea, cocoa, peach, and berries (Chen et al 2016). Furthermore, many reports have been issued on the effect of curry consumption on heavy metal induced toxicity.…”
Section: Discussionmentioning
confidence: 99%